Penggunaan Ungkapan Beri-Terima Bahasa Jepang dalam Novel Shiro no Naka no Hito Karya Hoshi Shin'ichi - Ana Wuri Retnaningrum (Universitas Dian Nuswantoro, 2019)
This paper discusses the use of yari-morai phrase (jujuhyougen) found in a novel data source titled Shiro no Naka no Hito. The purpose of this study is to describe the use of expressions of acceptance using Natsuko Tsujimura's theory. The items analyzed in this study are the function, role, and social distance of each argument. From the data analysis, it is found that when analyzed in a syntactic way, each argument functions as a subject and is a direct object or an indirect object. In semantic analysis, from the use of his verb, every argument plays the role of agent and beneficiary. Whereas from the use of passive expressions, each argument acts as a source and a goal. If pragmatic analysis is used, the use of the expressions is influenced by the vertical distance. However, formal situations are more important than existing vertical distances. So that also affects the use of proper expressions.